MEDIA PEMBELAJARAN GOOGLE CLASSROOM DALAM MENINGKATKAN KEMANDIRIAN BELAJAR SISWA PADA MATA PELAJARAN BAHASA ARAB DI MASA PANDEMI COVID-19 - tamaji, sampiril taurus; Umroh, Ida Latifatul (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2024)
Online learning has an important role for education today, one of the institutions that uses online learning is SMK Darul Ulum Baureno. Online learning is not possible to be carried out optimally if you do not use Google Classroom because so far Google Classroom has many advantages that are easily accessible to teachers and students at SMK Darul Ulum such as very mobile friendly for beginners, easy to send assignments and so on. This research is a type of library research, which is research whose object of study uses library data in the form of books as a source of data. The purpose of this study is to find out the Google Classroom learning media in increasing learning independence in Arabic subjects during the COVID-19 pandemic. The results obtained state that Google Classroom is an application developed by the google company. With this application, teachers and students from any school can communicate in a much simpler way. One of the strengths of Google Classroom is that it allows paper savings because the work or documents used in class will be shared digitally. Besides being easy to use in the Google Classroom application, it presents a variety of features that support the process of learning activities, such as making automatic copies of documents for students, creating assignments and directly grading them.